A voice in the crowd: Broader implications for crowdsourcing translation during crisis. (June 2013) - Sutherlin, Gwyneth
Both international non-governmental organizations and government actors have embraced the technological union of humans and software, known as crowdsourcing, to manage the flood of information produced during recent crises. However, unlike a business solution, the task of translation is unique during a crisis situation; the costs are human, and the impact is social and political. This paper follows four crises in which different crowdsourcing applications were developed by a range of actors. In each instance, the design approach failed to incorporate the unique circumstances of the conflict context, resulting in a translation application that removed authorship, dissolved intentionality, and shed contextual markers from original sources. This flawed application prevented the original contributors from interacting with the information directly related to their own life-threatening situation, and the information it amassed formed an unsound basis for decision-making by international actors. The associated consequences during: post-earthquake Haiti 2010, Libya and Egypt 2011 and Somalia 2011/12 are intended to provoke process improvement among all stakeholders.